High-performance liquid chromatographic assay for catecholamines and metanephrines using fluorimetric detection with pre-column 9-fluorenylmethyloxycarbonyl chloride derivatization - Chan, E.C.Y. (2014)
10.1016/S0378-4347(00)00423-0